Canboulay and the Negre Jardin - Patrick Murphy (Journal of Festive Studies)
Coming to terms with Trinidadian Carnival means dealing not only with its current manifestations but also with its often fraught history linked to imperialism and enslavement. A Catholic festivity, Carnival’s development is linked not only to European influences but also to African traditions and black-based activities that developed on the island prior to emancipation (1838). This article traces two such developments: Canboulay, a work procession carried out by the enslaved, which turned celebratory after abolition; and the negre jardin, the field laborer and also a Carnival character stereotyped by the elites, who was refurbished by black revelers after emancipation. The period analyzed is between the Spanish Cédula de Población of 1783, which spurred massive immigration, and the Canboulay Riots of 1881, which decisively contributed to Canboulay’s extinction. Although Canboulay was originally a procession linked to the recruitment of enslaved workers from multiple estates to labor on sugar plantations—or, at times, a form of enslaved rebellion—after emancipation, Canboulay shifted into a city-wide procession in which bands of revelers claimed the streets during Carnival. Similarly, if at first the negre jardin had been mockingly portrayed by the elites in their pre-emancipation celebrations, in the post-emancipation Carnival the figure reconfigured himself into a street-claiming character who marched through Port of Spain. Although both Canboulay and the negre jardin retained foundational characteristics of their pre-emancipation iterations—a necessary part of either manifestation—they also morphed into urban displays, tools for urban territorial takeovers, and cultural expressions that brought together Trinidadians through communal bonds.